Legal Enligtenment for Communities Affected by Illegal Online Loans and Online Gambling In Meruyung Village, Depok City - Mulyadi, Mulyadi; K, Kayus Leoleba; Ediani, Fasya Millatina; Putri, Adira; Manuel , Vedro (Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service activities in Meruyung Village, Depok City, focus on providing legal enlightenment to people affected by illegal online loans and online gambling. The main aim of this program is to increase public legal awareness regarding the negative impacts and legal consequences of engaging in illegal online lending and online gambling activities. The activity method is socialization and education through seminar activities. The community is provided with knowledge about the laws governing online loans and online gambling, including risks and how to identify legal and safe loan services. Before carrying out administrative activities, information is provided to residents about the material that will be delivered later. Education for increase public awareness regarding the dangers of illegal online loans and online gambling. The results achieved by these community services have made the public more aware of the dangers and legal consequences of illegal online loans and online gambling.  As a result, the plan is to hold a collaboration between the Meruyung sub-district and UPNVJ, there are people who are victims of illegal online loans and online gambling to get the legal assistance needed to resolve their problems. After carrying out this outreach activity, it is hoped that in the future the Meruyung sub-district community will see a significant reduction in the number of online loan cases. illegal and online gambling